2015
DOI: 10.1186/s13071-015-1226-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted silencing of the Aquaporin 2 gene of Rhipicephalus (Boophilus) microplus reduces tick fitness

Abstract: BackgroundTicks are blood-feeding arthropods that can affect human and animal health both directly by blood-feeding and indirectly by transmitting pathogens. The cattle tick Rhipicephalus (Boophilus) microplus is one of the most economically important ectoparasites of bovines worldwide and it is responsible for the transmission of the protozoan Babesia bovis, the etiological agent of bovine babesiosis. Aquaporins (AQPs) are water channel proteins implicated in physiological mechanisms of osmoregulation. Member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…We are entering an era where our understanding of how ticks evade vaccination and immune responses with their highly repetitive genomes, and how to formulate our vaccines to ensure that protective epitopes remain accessible is vital. To date, only two examples of promising combinatorial vaccines are known that of BM86 and subolesin and the peptide vaccine derived from a RV approach (Table ) . Although not fully understood, the functions of BM86 and Subolesin are most likely to be different based on the phenotypes observed after vaccination with individual antigens and the subcellular localization of the antigens.…”
Section: Insight From Tick Protein Evolution: Targeting Of Binding Spmentioning
confidence: 99%
“…We are entering an era where our understanding of how ticks evade vaccination and immune responses with their highly repetitive genomes, and how to formulate our vaccines to ensure that protective epitopes remain accessible is vital. To date, only two examples of promising combinatorial vaccines are known that of BM86 and subolesin and the peptide vaccine derived from a RV approach (Table ) . Although not fully understood, the functions of BM86 and Subolesin are most likely to be different based on the phenotypes observed after vaccination with individual antigens and the subcellular localization of the antigens.…”
Section: Insight From Tick Protein Evolution: Targeting Of Binding Spmentioning
confidence: 99%
“…Larger scale proteomic approaches have been used to identify proteins in R. microplus ovaries (68) and gut (69) of engorged females in response to infection with Babesia bovis. Out of these proteomic studies, several anti-tick vaccine antigens were identified and tested in vitro and in vivo (33,70). As the relationship between transcript and protein abundance is not direct and cannot reliably be predicted, proteomic and transcriptomic provide complementary information and are not redundant.…”
Section: Omics Approaches In Tick Vaccine Developmentmentioning
confidence: 99%
“…In addition, there can be physiological issues (99) responsible for the variable efficacy of the vaccines based on Bm86 antigen. Other concealed antigens that have been evaluated for efficacy against the cattle tick are the ribosomal protein P0, showing 96 % efficacy in pen trial (100), Subolesin, showing efficacy from 0-86 % (4), and 68 and 75 % with aquaporin (33,101). The antibodyantigen recognition process is poorly understood in the tick gut, hemolymph, and the intracellular space where tick digestion occurs.…”
Section: Perspectivementioning
confidence: 99%
“…Thirty adult females were injected with 0.2 L ferritin 1 dsRNA (9.74 × 10 11 molecules of dsRNA) between the coxa and trochanter I using a nanoinjector (Nanoject, Drummond Scientific, Broomall, PA, USA). The control group was injected with the same volume of elution buffer, similar to what has been described in other studies (Duscher et al, 2014;Hussein et al, 2015). Whilst the use of unrelated dsRNA is now a well-established control in species with full genome annotation, the R. sanguineus genome is poorly annotated, meaning inoculation with unconfirmed unrelated sequences can increase the off target effects in silencing experiments with this species.…”
Section: Dsrna Synthesis and Rna Interferencementioning
confidence: 99%